PERILAKU POLIAMORI DALAM “ DETRUIRE DIT-ELLE KARYA MARGUERITE DURAS - irianti Bandu; Prasuri Kuswarini (Universitas Hasanuddin, 2017)
The title of this research is The Poliamori Behaviour in “Detruire Dit-Elle“ Novel byMarguerite Duras. This research analyze about the poliamori behaviour by the characters.The aim of this research are to describe and explain the poliamori relationship betweenAlissa, Max Thor and Stein in “Detruire dit-elle” novel. Alissa is the wife of Max Thorhas the romantic relationship with Stein. However, Max Thor is not questioning thatrelationship and accept it. The research uses the characterization theory and love theoryFromm.In this research, the writer explains about the important characters in the novel. Then, thewriter sorts the events which are considered as the poliamori behaviour by the characters.The last, the writer analyzes the data and features the erotic love affair by which is doneby third character.The result of this research shows that Alissa, Max Thor and Stein are done thepoliamori relationship based on the love concept that is classified as a care attitude(attention) intimacy and physical closeness factors.Keys Words: behavior, polyamory, character, love